Nutritional Aspects to Prevent Heart Diseases in Traditional Persian Medicine - Gholamreza Kordafshari MD (Journal of Evidence-Based Complementary & Alternative Medicine, 2015)
Cardiovascular diseases are major health complications currently in various societies. Management of heart diseases as a prevention step or as treatment with low-cost procedures like lifestyle modifications including nutrition are important current trends. Although the term nutrition dates back to 2 past centuries, Persian physicians contributed to this term at least from 1000 years ago. Rhazes (865-925 AD) was one of the pioneers in this field. He preferred using foods in treating illnesses. “Foods and drinks” were 1 subject from 6 principles ( Setteh Zarorieh ) that Persian physicians believed can affect human health. In this review, we described some medieval Persian views on the role of nutrition in heart diseases and compare their prescriptions with current findings. Interestingly, current investigations mostly support Persian medicine principles. Historically, this work shows that the concept of nutrition in heart diseases has had a successful background at least from 1000 years ago in Persia.